Strategi Peningkatan Kesuburan Lahan Melalui Optimalisasi Pupuk Organik Untuk Meningkatkan Produktivitas Tanaman Indigofera zollingeriana Skala Lapang: Strategy to Improve Land Fertility Through Optimization of Organic Fertilizer to Improve Productivity of Indigofera zollingeriana Plant on Field Scale - Prihantoro, Iwan; Panca Dewi Manuhara Karti; Siregar, Fadil Muhammad (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
This study aimed to evaluate the effect of manure on the production and nutrients of Indigofera zollingeriana legumes on a field scale. This study used a completely randomized design (CRD) with 6 treatments (FS0 = 0 ton ha-1 manure, FS5 = 5 ton ha-1 manure, FS10 = 10 ton ha-1 manure, FS15 = 15 ton ha-1 manure, FS20 = 20 ton ha-1 manure, FS25 = 25 ton ha-1 manure) and 5 replications. The data obtained were tested using analysis of variance (ANOVA) and if there was a significant difference, it was continued with the Duncan test. The results showed that the use of manure effectively increased (p<0.05) soil pH, number of leaves, plant height, stem circumference, number of branches, fresh biomass production, dry biomass, leaf stem ratio, and nutrient biomass (crude protein and crude fiber), but has not been able to improve the nutrient quality of Indigofera zollingeriana on a field scale. It can be concluded the use of manure at a level of 25 tons ha-1 resulted in the best production of Indigofera zollingeriana plants.